2021
DOI: 10.1016/j.sapharm.2020.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Drive-thru pharmacy services: A way forward to combat COVID-19 pandemic

Abstract: Countries around the globe have responded to pandemic preparedness and developed strategies to cope with the COVID-19 crisis. In this context, the role of healthcare professionals is of paramount importance. Pharmacists are playing a vital role in dealing, preparedness, prevention, protection, promoting access to medicines and to improve health outcomes during this crisis. In this context, “Drive-thru” pharmacy services improve access to medicines while ensuring the preventive measures suggested by the World H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 20 publications
(29 reference statements)
0
56
0
4
Order By: Relevance
“…Before COVID-19, community pharmacies globally were offering “valued-added services” (VAS) such as drive-thru services, online ordering and communications services (e.g., prescription reminders) to stay competitive. Many VAS services have helped pharmacies adapt more quickly to pandemic restrictions 81 .…”
Section: Resultsmentioning
confidence: 99%
“…Before COVID-19, community pharmacies globally were offering “valued-added services” (VAS) such as drive-thru services, online ordering and communications services (e.g., prescription reminders) to stay competitive. Many VAS services have helped pharmacies adapt more quickly to pandemic restrictions 81 .…”
Section: Resultsmentioning
confidence: 99%
“…In line with the WHO guidelines during the outbreak of COVID-19 pandemic in 2020 [33], elderly patients, who are associated with higher risks of mortality with coronavirus infection [34], are encouraged to select drive-through services in order to avoid the crowds and limit the contact with others [35]. Drive-through pharmacy also has been encouraged locally and in Australia during the on-going pandemic of COVID-19 as a safety measure for the public especially the elderly to get their medication because the nature of this service enables the practice of physical distancing and it has been a proven e cient and safe method of medication dispensing [35,36]. In spite of many advantages of drive-through services, it is important to note that this service would be of maximum bene t for citizens who own a vehicle and when the hospital is faced with inadequate carparks [37][38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…They reported that these drive-through visits provide services that were not possible through telehealth and remote examinations, while reducing the need for clinical visits and thus reducing the anxiety of patients who prefer face-to-face visits. Drive-through facilities have also been expanded and used for providing pharmacy services during COVID-19 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%